Celiac Plexus Block for Treatment of Pain Associated with Pancreatic Cancer: A Meta‐Analysis. Issue 1 (20th May 2013) - Zhong, Wa; Yu, Zhong; Zeng, Jing‐Xian; Lin, Ying; Yu, Tao; Min, Xiao‐Hui; Yuan, Yu‐Hong; Chen, Qi‐Kui
Abstract Pancreatic ductal adenocarcinoma has a high rate of neural invasion (80 to 100%) and can be associated with moderate to severe pain in pancreatic cancer. Treatment of pain with celiac plexus blockage (CPB) combined with the three‐step ladder utilization of pharmaceutical analgesics following WHO guidelines is used, but the evidence in randomized controlled trials is inconsistent. This meta‐analysis identified and compared seven randomized control trials of pain relief from pancreatic cancer, by treatment with medical management alone to celiac plexus blockade with medical management. While no evidence of potential publication bias was detected, group size and statistical power may account for some of the inconsistent conclusions. The combined CPB groups had a significantly lower pain score at 4 weeks, but significance was not maintained at 8 weeks. The combined CPB groups required significantly less drug use compared to the combined control groups treated with pharmaceutical analgesics.